PT INDOFOOD SUKSES MAKMUR TBK: ANALISIS TREN SOLVABILITAS DAN AKTIVITAS KEUANGAN SELAMA 2021-2023 - Kharisma, Enggar Dwi (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to analyze the solvency trends and financial activities of PT Indofood Sukses Makmur Tbk during the 2021-2023 period. The financial ratios used in this study include Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Fixed Assets Turnover (FAT), and Total Assets Turnover (TAT). A quantitative descriptive approach is applied to evaluate audited financial statement data. The results of the analysis show that the company's DAR has decreased from year to year, from 51% in 2021 to 46% in 2023, reflecting a reduction in the company's dependence on debt for asset funding. Similarly, DER decreased from 106% in 2021 to 85% in 2023, indicating an increase in the proportion of equity-based funding. In terms of activity, FAT shows an increase in efficiency in the use of fixed assets, with the ratio rising from 2.12 times in 2021 to 2.36 times in 2023. However, TAT fluctuated, with an increase in 2022 but a slight decrease again in 2023. This fluctuation indicates that there is room for improvement in the utilization of total assets to generate sales. This finding suggests that while the company has demonstrated good solvency management, improving the efficiency of total asset activity remains a challenge. With solvency ratios close to industry standards and activities still below benchmark, this study provides important insights for the company in improving its financial management to support sustainable growth.